Ground-state g factor of middle-Z boronlike ions. (November 2018) - Agababaev, V A; Glazov, D A; Volotka, A V; Zinenko, D V; Shabaev, V M; Plunien, G
Abstract: Theoretical calculations of the interelectronic-interaction and QED corrections to the g factor of the ground state of boronlike ions are presented. The first-order interelectronic-interaction and the self-energy corrections are evaluated within the rigorous QED approach in the effective screening potential. The second-order interelectronic interaction is considered within the Breit approximation. The nuclear recoil effect is also taken into account. The results for the ground-state g factor of boronlike ions in the range Z = 10-20 are presented and compared to the previous calculations.